Catalytic and anti-bacterial properties of biosynthesized silver nanoparticles using native inulin. Issue 50 (14th August 2018) - Xu, Wei; Huang, Kunling; Jin, Weiping; Luo, Denglin; Liu, Huan; Li, Yingying; Liu, Xinfang
Abstract : Silver nanoparticles (Ag NPs) were green synthesized using native inulin as the reducing and capping agent with varied incubation temperatures, incubation times and Ag + concentrations. Abstract : Silver nanoparticles (Ag NPs) were green synthesized using native inulin as the reducing and capping agent with varied incubation temperatures, incubation times and Ag + concentrations. The biosynthesized Ag NPs were characterized using UV-visible spectroscopy, Field Emission Transmission Electron Microscopy (FE-TEM) and X-ray powder diffraction. The UV visible spectra of the Ag NPs revealed a characteristic surface plasmon resonance peak at 420 nm. FE-TEM showed that the biosynthesized Ag NPs were spherically shaped and monodispersed nanoparticles. The sizes were 18.5 ± 0.9 nm and 20.0 ± 1.2 nm for the Ag NPs synthesized at 80 °C and 100 °C for 2 h using 0.1% inulin and 2 mM Ag + . Their PDIs were 0.180 ± 0.05 and 0.282 ± 0.13, respectively. Improving the incubation temperature, incubation time and silver nitrate concentration promoted Ag NP synthesis. The prepared Ag NPs were effective in the catalytic reduction of 4-NP and in inhibiting the growth of bacteria. The inhibition zone could reach 10.21 ± 2.12 mm and 9.92 ± 0.50 mm for Escherichia coli and Staphylococcus aureus . The kinetic rate constant ( k app ) could reach 0.0113 s −1, and the maximum inhibitory zones were 10.21 ± 2.12 mm and 9.92 ± 0.50 mm, respectively, for the two microorganisms. This biosynthesis illustrates that native inulin could be a potential candidate in the green fabrication of Ag NPs, and this is promising in catalytic and bacteriostatic fields.